Siglec-H protects from virus-triggered severe systemic autoimmunity - Schmitt, Heike; Sell, Sabrina; Koch, Julia; Seefried, Martina; Sonnewald, Sophia; Daniel, Christoph; Winkler, Thomas; Nitschke, Lars (Journal of Experimental Medicine, 2016)
It is controversial whether virus infections can contribute to the development of autoimmune diseases. Type I interferons (IFNs) are critical antiviral cytokines during virus infections and have also been implicated in the pathogenesis of systemic lupus erythematosus. Type I IFN is mainly produced by plasmacytoid dendritic cells (pDCs). The secretion of type I IFN of pDCs is modulated by Siglec-H, a DAP12-associated receptor on pDCs. In this study, we show that Siglec-H-deficient pDCs produce more of the type I IFN, IFN-alpha, in vitro and that Siglec-H knockout (KO) mice produce more IFN-alpha after murine cytomegalovirus (mCMV) infection in vivo. This did not impact control of viral replication. Remarkably, several weeks after a single mCMV infection, Siglec-H KO mice developed a severe form of systemic lupus-like autoimmune disease with strong kidney nephritis. In contrast, uninfected aging Siglec-H KO mice developed a mild form of systemic autoimmunity. The induction of systemic autoimmune disease after virus infection in Siglec-H KO mice was accompanied by a type I IFN signature and fully dependent on type I IFN signaling. These results show that Siglec-H normally serves as a modulator of type I IFN responses after infection with a persistent virus and thereby prevents induction of autoimmune disease.

Targeting Human CD22/Siglec-2 with Dimeric Sialosides as Novel Oligosaccharide Mimetics - Prescher, Horst; Schweizer, Astrid; Frank, Martin; Kuhfeldt, Elena; Ring, Julia; Nitschke, Lars (Journal of Medicinal Chemistry, 2022)
Significant interest in the development of high-affinity ligands for Siglecs exists due to the various therapeutically relevant functions of these proteins. Here, we report a new strategy to develop and design Siglec ligands as disialyl-oligosaccharide mimetics exemplified on Siglec-2 (CD22). We report insights into development of dimeric ligands with high affinity and avidity to cell surface-expressed CD22, assay development, tool compounds, structure activity relationships, and biological data on calcium flux regulation in B-cells. The binding modes of selected ligands have been modeled based on state-of-the-art molecular dynamics simulations on the microsecond timescale, providing detailed views on ligand binding and opening a new perspective on drug design efforts for Siglecs. High-avidity dimeric ligands containing a linker opening the way towards bispecifics are presented as well.
CRIS-Team Scopus Importer:2022-09-02